Migraciones y codesarrollo - Carballo, Marta (Revista Española de Desarrollo y Cooperación, 2023)
In the present article the authoress reviews how the concept of codevelopment has been developed since 1998 as a part of public policies in different scenarios, and how the different definitions have been modified. The aim of the article is to suggest a new definition that includes the existing diversity, and to conclude with some notes on the current moment and the possible routes to articulate the concept of codevelopment.